Cancer control in the first level: The role of rural nurses in low-income settings - Luxardo, Natalia (2018)
This article is aimed at providing insights into the experiences of rural nurses? and their perceptions in relation to disciplinary values, particularities of the cultural context,institutional constraints in such settings, and the effects of other health systems on the day-to-day healthcare practices carried out in low-resource health centres.This study is based on a framework of equity used to explain such differences in access to preventive and adequate care, which result in different rates of morbidityand mortality among regions. Many researchers provide evidence to support the idea that persistent lack of accessible, affordable, and culturally relevant programsfor cancer prevention and health promotion among medically underserved and historically marginalised populations are strongly associated with cancer disparities.Among underserved populations, rural communities are particular vulnerable in getting access to adequate cancer care. The daily work of nurses in rural settings canprovide clues to help understand what happens between the broader organisation of care system directives and the daily routines carried out in health centres.